Heterotopic Ossification with Classical Hodgkin Lymphoma in a Surgical Incision: A Case Report - Faro, Bárbara Loeser; Silva, Leonardo Fleury da; Mizoguti, Nathalia Nakase; Medeiros, Ana Carolina; Wolski, Mariana Marques; Vellozo, Fernando Andrade; Nasr, Adônis (Brazilian Journal of Case Reports, 2025)
Heterotopic ossification (HO) is the formation of bone tissue in areas where bone does not normally exist. It most commonly affects soft tissues after orthopedic surgeries involving major joints and is a rare complication of abdominal surgeries. When heterotopic ossification is excised, histopathological and immunohistochemical studies are essential to assess and rule out neoplastic tissue. Hodgkin lymphoma (HL) is a lymphoproliferative neoplasm characterized by the proliferation of morphologically and immunophenotypically altered cells, derived from the malignant transformation of germinal center B lymphocytes. Less commonly, patients with classical HL may also present with other very rare manifestations, such as heterotopic ossification. This case report aims to present a heterotopic ossification found in the preperitoneal space of a midline incision during laparotomy for retroperitoneal lymph node biopsy due to suspected lymphoproliferative disease, with a rare immunohistochemical result consistent with classical Hodgkin lymphoma.